Erythrocyte Associated Amyloid-β as Potential Biomarker to Diagnose Dementia - Lauriola, Michele; Paroni, Giulia; Ciccone, Filomena; D'Onofrio, Grazia; Cascavilla, Leandro; Paris, Francesco; Gravina, Carolina; Urbano, Maria; Seripa, Davide; Greco, Antonio (Current Alzheimer Research, 2018)
Background: Although it is known that Alzheimer's disease (AD) is associated with the progressive accumulation of amyloid β-peptide (Aβ) in the human brain, its pathogenic role has to be completely clarified. Aβ moves from the bloodbrain barrier to the plasma and an increased Aβ production in brain could be associated with higher Aβ concentrations in blood. A recent study has evaluated Aβ40 and Aβ42 levels in human red blood cells (RBCs) with evidence of agedependent higher Aβ concentration in RBCs. Objective: The aim of the study was to investigate if erythrocyte associated Aβ (iAβ) levels could be different in subjects affected by dementia in comparison with controls and according to the patient’s cognitive impairment or different dementia subtypes. Method: To answer these questions we assessed iAβ40 and iAβ42 levels in 116 patients: 32 healthy controls, 39 with diagnosis of vascular dementia (VaD), 14 mild cognitive impairment (MCI) and 31 AD. Results: In this population we found significant differences in iAβ42 between controls and cognitive impaired patients. Moreover, iAβ42 significantly differed between dementia vs MCI. AD also showed different iAβ42 levels as compared to VaD. Conversely, no differences were found for iAβ40. All the analyses were adjusted for potential confounders like age, gender and Hb concentration. A direct correlation between increasing iAβ42 concentration and the progression of the cognitive decline using the MMSE score as continuous variable was also found. Conclusion: Our findings support the evidence that iAβ42 could be an instrument to early recognize dementia and predict cognitive impairment.
Keywords: cognitive impairment